Students' understanding of physical culture and sports as a factor of health protection - Taras Bondar; Iryna Holoviichuk (Kharkiv State Academy of Physical Culture, 2019)
Purpose: determination of the state of the relationship between students' knowledge on the factors of maintaining human health and the real state of their physical culture and sports activities. Material & Methods: students from the specialties "Finance", "Banking and Insurance", "Economics", "Accounting and Taxation", "Management", "Psychology", "Law" took part in a sociological study. Results: in the process of analyzing the survey data it was found that on the one hand, most students are aware of the factors of maintaining health and the benefits of physical activity to strengthen it. On the other hand, only a small part of students consciously use physical exercises to strengthen their own body. Conclusions: the results obtained during the study showed that there is a need to improve pedagogical and organizational and managerial work on physical culture and sports leisure for children and youth, in particular, their involvement in modern forms of outdoor activities.